EXPERIMENTAL ANALYSIS OF A HEAT PUMP ASSISTED RECUPERATIVE AIR DEHUMIDIFIER - Pereira, C. A. B.; Pereira, R. H.; Marques, R. P.; Parise, J. A. R.; Sodré, J.R. (Revista de Engenharia Térmica, 2004)
This paper describes the experimental analysis of a heat pump assisted recuperative air dehumidifier. The system consisted of an air-to-air vapor compression heat pump, coupled to the air ducting. Dehumidification was generated by reduction of the air temperature through the evaporator below the dew point, and thus promoting the condensation of the water vapor. Moist air was then warmed up in the condenser, resulting in a lowtemperature low-humidity air stream. Low energy consumption values are achieved in such systems as the latent heat of the water vapor acts as the heat pump own heat source. Occasionally, the compressor heat is also recoverable. The innovative feature of the present analysis was the introduction of an air-to-air plate recuperator, to further promote dehumidification, yet at the expense of greater compressor energy consumption. An experimental apparatus was constructed to perform comparative tests of the dehumidifier operating with and without the recuperator. A closed air circuit was employed, with the air mass flow rate as the controlling parameter of the experiment. Tests were also carried out with an open circuit.